Peran Program Literasi Sejarah dalam Meningkatkan Minat Belajar Sejarah Kebudayaan Islam (SKI) Siswa Kelas XI di MAN 2 Kota Bogor - Yola Oktariana; Milla, Sri Nurul; Rosidah , Noneng Siti (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this research is to know and describe the implementation of the historical literature program in MAN 2 Bogor City and to know the role of the history literature programme in increasing the interest of students of XI MAN 2 City Bogor class in learning SKI. This type of research is qualitative research. The source of the research data is the deputy head of the curriculum school, the teacher of the Islamic cultural history lesson, and eleventh-grade students. Data obtained through interviews, and documentation. The findings in this study first, the implementation of historical literature in MAN 2 Bogor City, namely through reading books 15 minutes before the start of learning, book surgery, role play, interactive discussions and screenings of history films. Then second, the role of history literacy in increasing student learning interest in learning SKI showed that the history literature program can grow students' interest in the culture of historic literature, train students to engage actively in the classroom. It adds insight into the history of Islamic culture and raises concern about the importance of the Islamic cultural history. The development of this historical literacy program must be continued accurately and effectively in order to give an optimal impact by the school institution and teachers are expected to be able to adjust learning strategies, both learning methods or learning atmosphere so that students continue to be motivated and able to maintain and improve literacy skills to understand SKI learning well